THE SECONDARY SCHOOL STUDENTS’ VIEWS ABOUT THE EFFECTIVENESS OF TEOG EXAM ON ENGLISH LANGUAGE LEARNING - Mehmet Nuri GÖMLEKSİZ (Fırat University, 2019)
In our country, while passing from secondary school to high school, an exam called Transition from Primary Education to Secondary Education System (TEOG) is carried out and all 8th grade students have to take this exam. Students are enrolled a high school based on their choices in line with the scores they get from TEOG exam. In this exam, students are asked about English besides Mathematics, Turkish Language, Science, Social Studies, Religious Culture and Moral Knowledge courses. The aim of this study is to determine secondary school students’ views about the effectiveness of TEOG exam on English language learning. In this direction, the students’ views about reading and comprehension an English text were determined. Moreover, their views about the effectiveness of TEOG exam outcomes on their speaking with their teachers and friends; the effect on their listening and understanding a song, film, dialogue, drama activities in English; and the effect on their vocabulary were also determined. In this study, qualitative research design was used. The study group consisted of the students enrolled at three state schools in Elazığ city center in 2016-2017 academic year. Maximum variation sampling method was used in the study. In determination of schools, the socio-economic standards were considered, and three schools were determined as high, middle and low socio-economic status. From each school six students were selected and totally 18 students were included in the study. In determination of socio-economic status of schools, the locations of these schools and the views of officials from Provincial Directorate of National Education were considered. Volunteer students participated to the study. Study results revealed that TEOG exam had a positive impact on English language learning. Several recommendations are offered based on the research findings.